Distinct domains in Ndc1 mediate its interaction with the Nup84 complex and the nuclear membrane - Amm, Ingo; Weberruss, Marion; Hellwig, Andrea; Schwarz, Johannes; Tatarek-Nossol, Marianna; Lüchtenborg, Christian; Kallas, Martina; Brügger, Britta; Hurt, Ed; Antonin, Wolfram (The journal of cell biology, 2023)
Nuclear pore complexes (NPCs) are embedded in the nuclear envelope and built from ∼30 different nucleoporins (Nups) in multiple copies, few are integral membrane proteins. One of these transmembrane nucleoporins, Ndc1, is thought to function in NPC assembly at the fused inner and outer nuclear membranes. Here, we show a direct interaction of Ndc1’s transmembrane domain with Nup120 and Nup133, members of the pore membrane coating Y-complex. We identify an amphipathic helix in Ndc1’s C-terminal domain binding highly curved liposomes. Upon overexpression, this amphipathic motif is toxic and dramatically alters the intracellular membrane organization in yeast. Ndc1’s amphipathic motif functionally interacts with related motifs in the C-terminus of the nucleoporins Nup53 and Nup59, important for pore membrane binding and interconnecting NPC modules. The essential function of Ndc1 can be suppressed by deleting the amphipathic helix from Nup53. Our data indicate that nuclear membrane and presumably NPC biogenesis depends on a balanced ratio between amphipathic motifs in diverse nucleoporins.
Online veröffentlicht: May 08 2023
Gesehen am 20.07.2023